2003
DOI: 10.28945/2619
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Computer Ethics into the Computing Curriculum: A Framework for Implementation

Abstract: The advent of the Information Age and global connectivity has placed ethics center stage in the use of Information and Communication Technologies (ICT). As the drive towards the establishment of a socalled IT profession gains momentum, ethical conduct and codes of ethics have recently been formulated and introduced formally. Initiatives in this regard can be attributed to, among others, the ACM and the IEEE. Of particular significance is the ImpactCS Project commissioned by the joint taskforce of the ACM and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Academic disciplines usually have assumptions and principles which tend to be emphasised more in the curricula than other external requirements (Hammond & Bennett, 2002). Barnard, De Ridder, Pretorious, and Cohen (2003) also confirm that departmental pragmatics and logistics can have a major influence on the approach adopted for the curricula development. Participant (L4) in the present study stated that:…”
Section: Factors Influencing Curriculum Developmentmentioning
confidence: 86%
“…Academic disciplines usually have assumptions and principles which tend to be emphasised more in the curricula than other external requirements (Hammond & Bennett, 2002). Barnard, De Ridder, Pretorious, and Cohen (2003) also confirm that departmental pragmatics and logistics can have a major influence on the approach adopted for the curricula development. Participant (L4) in the present study stated that:…”
Section: Factors Influencing Curriculum Developmentmentioning
confidence: 86%
“…To conduct ethics education instruction, the teacher needs to be aware of ethical and social issues technology is likely to confront the society with [17]. Therefore, such awareness should go beyond just the knowledge of principles prescribed by the codes of ethics, but also competently lead students through the ethical analysis learning process [35].…”
Section: B Teachers As Facilitators Of Ethical Awarenessmentioning
confidence: 99%
“…Several studies such as those conducted by [25], [48]- [51] studied ethical awareness on students but do not determine if those who are instructing the students, do have the ethical awareness required to teach the students and what their impact is on the students. Barnard et al [17] have demonstrated that computing instructors regard the teaching of computer ethics as importantly equal to the teaching of technological topics. We, therefore find it important to determine the extent to which lecturers involved in the teaching of software development are aware of software engineering codes of ethics, which are necessary and in some cases prescribed to instruct students.…”
Section: Research Advances On Software Engineering Code Of Ethics Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2001, different CS/IS departments have included computer ethics topics in their curricula. Various computer ethics topics have also been addressed by local researchers, for example (Britz, Boekhorst & Bothma, 2002;Charlesworth & Sewry, 2002;Lipinski, Buchanen & Britz , 2002;Pretorius, Barnard & De Ridder, 2002;Barnard, De Ridder, Pretorius & Cohen, 2003;Cloete, Pretorius & Barnard, 2003).…”
Section: Recent South African Computer Ethics Initiativesmentioning
confidence: 99%